USING CANVA AS MEDIA FOR ENGLISH LANGUAGE TEACHING (ELT) IN DEVELOPING CREATIVITY FOR INFORMATICS STUDENTSâ€™ - Tira Nur Fitria (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
This research simulates the use of Canva as a medium for English Language Teaching (ELT) in developing the creativity of Informatics Students in English for Working Course at ITB AAS Indonesia. This research is descriptive qualitative. The result analysis shows that educators (teachers or lecturers) can use the Canva application in English Language Teaching (ELT) such as creating materials for job vacancies, cover letter/job application letter, curriculum vitae (CV) or resume in English for Working subject to the students. In creating materials for â€œJob Vacancyâ€, we can use a template or layout of brochures, flyers, or announcements. Canva is very suitable to be used for learning basic competencies about functional texts, including functional texts to make brochures/flyer/announcement, letter, and curriculum vitae (CV) or resume by editing the existing text in the Canva application and then changing it with their words according to the situation requested by the teacher. Canva is hoped can develop and grow students' creativity in the field of technology by designing their designs, adding text, adding images, or adding photos. Canva application is very easy to practice and suitable for students majoring in Informatics students who want to learn to make simple graphic designs creatively and innovatively.